Identification and antifungal activity analysis of two biocontrol antagonists to Colletotrichum musae. Issue 7 (14th June 2017) - Shu, Canwei; Chen, Qiguang; Pi, Lei; Zhang, Detao; Panhwar, Qurban Ali; Zhou, Erxun
Abstract: Postharvest anthracnose of banana caused by Colletotrichum musae is one of the major diseases resulting in huge economic losses worldwide. To control this disease using biocontrol agents, two antagonistic strains SD7 and NB20 with significant inhibitory effects on mycelial growth and conidial germination of C. musae were identified and evaluated in this study. The inhibitory effects of cell‐free culture filtrates of SD7 and NB20 on conidial germination of C. musae were both 100%, and those on mycelial growth of C. musae were 97.7 ± 0.9% and 95.0 ± 0.6%, respectively. The antifungal activities of cell‐free culture filtrates of both strains were still stable after they were stored at 4°C for 6 months. The control efficacies of cell‐free culture filtrates of SD7 and NB20 on postharvest anthracnose of banana were 55.9 ± 4.1% and 33.2 ± 3.9%, respectively. The disease severity (mean scale value) in banana fruit fingers was significantly lower after the treatment with a cultural suspension of the bacterial strain SD7 (1.4 ± 0.49) or actinomycete strain NB20 (2.0 ± 0.63), compared to that in the control (4.8 ± 0.40). After subculturing for 10 generations, the antifungal efficiency of NB20 remained stable, whereas that of strain SD7 declined obviously. Lastly, based on the morphological, physio‐biochemical and molecular characteristics, the bacterial strain SD7 was identified as Burkholderia cepacia, while the actinomycete strain NB20 was identified as Streptomyces katrae . The results from this study will provide the basis for developing an effective and novel biofungicide to control banana anthracnose disease.